The Strange Death of Marxism : The European Left in the New Millennium - Gottfried, Paul, 1941- (Book collections on Project MUSE., 2005)
"Describes a twentieth-century transformation in European leftist and Marxist politics. European Marxism began as an economically focused workers' movement, then became the domain of those desiring cultural transformation of Western Europe. The transformation emphasizes Western European guilt and promotes multiculturalism, feminism, and acceptance of alternative lifestyles condemned by European cultures"--Provided by publisher.